The legal organization of the Independent High Electoral Commission between independence and Censorship in Iraq - Al-Abbasi, Yassin Myasar Aziz Ali (Arab Journal for Sciences and Research Publishing, 2017)
The transmission of Iraq to democracy (in a crucial stage in his modern history ) required recourse to the mechanisms that activate the political representation through free and fair democratic elections that express the will of people to choose their rulers, actually what has been achieved in Iraq is an unprecedented leap, stipulated by the permanent Iraqi constitution of 2005, through developing one of the constitutional institutions to the elections by describing it as an independent body, in which the elections commissions play actually an important role in reinforcing the stability and especially in the emerging democracies, through the elective operations performing by the institutions and in which the people can express its opinion by choosing its representative. Although three elections for the province's council were performed as well as the referendum on the constitution and the elections of Iraq parliament for 3 sessions and the elections of president and parliament in Kurdistan The constitution entrusted the censorship on the work of the commission to the legislative authority presented by the parliament and it returns the organization of the work of the commission to a law legislated by the parliament-without determining restrictions or controls –related to its formation, jobs or powers. Does this law satisfy the ambitions and hopes of the constitution and devotes the independence of the entity toward legislative authority itself? Or it jumps higher than these ambitions. One of the ways of supervising on the work of the commission where these monitoring tools was mentioned in the constitution and referred to the parliament gain the right to follow and monitor the independent entities and one of it the higher independent commission of election through a group of methods of surveillance ranging by the way of using the right of asking and then questioning and the way of nominating and dismissal the members of the commission board referred to the constitutional text that organizes this. In addition to the monitoring role that the national and international institutions of civil society practice and the supervisors of the political entities participating in the electoral process other than monitoring the different means of media in accordance to the international standards and the special laws and regulations.
Keywords: Iraq; elections; constitution; politics; Independence and control; Independent High Electoral Commission